The Dark Knight Rises: Kita Butuh Simbol untuk Menggerakkan - Danu Widhyatmoko (Bina Nusantara University, 2013)
The dark knight rises: We Need Symbols to Make Movements is a writing that covers values existing in the last movie of Batman trilogy: The Dark Knight Rises (TDKR). In the film, it is described how batman is not only presented as a hero who saved the town, but also is presented as a symbol that keeps hope of the Gotham city society. Through this writing, it is also discussed the relation between TDKR and the recent condition of Indonesia.